ISSUES OF SPELLING, STYLISTICS AND LANGUAGE TEACHING METHODOLOGY IN THE WORKS OF V.G.GAK (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
V.G. The peculiarity of the Gak language teaching methodology is that the scientist tried to create educational materials that would allow everyone to master the French language in a short period of time. In this way, he achieved high results. Educational materials developed by V. G. Gak are still used in the pedagogical process today. The scientist believed that the ability to read a foreign language is of particular importance, regardless of all other language competencies. It allows you to read works of art previously known only through translations in their original form. V.G. Gak has demonstrated that you can learn to read French texts of moderate difficulty in a short time.In particular, the scientist L.A. Developed in cooperation with Murodova. "Learning to read in French. "Short Programming Guide" is designed to effectively solve this problem. This guide will allow you to learn to read and understand French text of moderate difficulty from periodicals in a few weeks without much effort. This book uses programmed learning elements and a specially developed original methodology, on the basis of which you can learn French grammar sufficiently completely and memorize more than 2000 words without referring to other textbooks and dictionaries.